"When my mother called me to say that the time of cutting had arrived, I just escaped to Belgium with my daughter": identifying turning points in the change of attitudes towards the practice of female genital mutilation among migrant women in Belgium - Afi A. Agboli; Fabienne Richard; Isabelle Aujoulat (BMC, 2020)
Abstract Background Female Genital Mutilation (FGM) is a public health concern with negative consequences on women's health. It is a harmful practice which is recognized in international discourses on public health as a form of gender-based violence. Women are not only victims of this, but also perpetrators. The practice of FGM remains a social norm which is difficult to change because it is deeply rooted in tradition and is embedded in the patriarchal system. However, some women have managed to change their attitudes towards it and have spoken out against it. This study identifies and describes turning points that have been defined as significant and critical events in the lives of the women, and that have engendered changes in their attitudes towards the practice of FGM. Methods We have conducted an inductive qualitative study based on the life story approach, where we interviewed 15 women who have undergone FGM. During the interviews, we discussed and identified the turning points that gave the research participants the courage to change their position regarding FGM. The analysis drew on lifeline constructions and thematic analysis. Results Six common turning points relating to a change in attitude towards FGM were identified: turning points related to (i) encounters with health professionals, (ii) education, (iii) social interactions with other cultures and their own culture, (iv) experiences of motherhood, (v) repeated pain during sexual or reproductive activity, and (vi) witnessing the effects of some harmful consequences of FGM on loved ones. Conclusions The turning points identified challenged the understanding of what it means to be a 'member' of the community in a patriarchal system; a 'normal woman' according to the community; and what it means to be a 'good mother'. Moreover, the turning points manifested in conjunction with issues centered on emotional responses and coming to terms with conflicts of loyalty, which we see as possible triggers behind the shift experienced by the women in our sample.